Moral Intelligence and Its Relationship to Social Responsibility and Achievement Motivation Among Jadara University Students - Anas Ramadan Al-Masri; Shorouq Muhammad Maabreh; Habis Muhammad Hatamleh (Technium Social Sciences Journal, 2020)
The study aimed at revealing moral intelligence and its relationship to social responsibility and achievement motivation among students at Jadara University. The random stratified sample consisted of (355) male and female students from Jadara University in Irbid.The researchers adopted the descriptive approach and used the following measures: the moral intelligence scale that they developed (Shawara, 2017); The social responsibility scale he developed (Al-Obeisat, 2017); The motivation scale of his achievement (Al-Essa, 2016). The findings showed that: 1) there is a statistically significant positive relationship between “moral intelligence” and “social responsibility and achievement motivation” among the students at Jadara University. The results also showed that there are statistically significant differences in moral intelligence and achievement motivation due to the variable, where the differences came in favor of the excellent. The results also indicated that there are statistically significant differences in moral intelligence and social responsibility attributable to the college variable, where the differences came in favor of the humanities college. The results also showed that there are statistically significant differences in achievement motivation attributable to the variable of the year of study and the differences came in favor of the fourth year.